Transcriptomic analysis of Arabidopsis thaliana plants treated with the Ky-9 and Ky-72 histone deacetylase inhibitors. (4th March 2018) - Nguyen, Huong Mai; Sako, Kaori; Matsui, Akihiro; Ueda, Minoru; Tanaka, Maho; Ito, Akihiro; Nishino, Norikazu; Yoshida, Minoru; Seki, Motoaki
ABSTRACT: Histone acetylation plays a pivotal role in plant growth and development, and is regulated by the antagonistic relationship between histone acetyltransferase (HAT) and histone deacetylase (HDAC). We previously revealed that some HDAC inhibitors confer high-salinity stress tolerance in plants. In this study, we identified two HDAC inhibitors, namely Ky-9 and Ky-72, which enhanced the high-salinity stress tolerance of Arabidopsis thaliana . Ky-9 and Ky-72 are structurally similar chlamydocin analogs. However, the in vitro inhibitory activity of Ky-9 against mammalian HDAC is greater than that of Ky-72. A western blot indicated that Ky-9 and Ky-72 increased the acetylation levels of histone H3, suggesting they exhibit HDAC inhibitory activities in plants. We conducted a transcriptomic analysis to investigate how Ky-9 and Ky-72 enhance high-salinity stress tolerance. Although Ky-9 upregulated the expression of more genes than Ky-72, similar gene expression patterns were induced by both HDAC inhibitors. Additionally, the expression of high-salinity stress tolerance-related genes, such as anthocyanin-related genes and a small peptide-encoding gene, increased by Ky-9 and Ky-72. These data suggest that slight structural differences in chemical side chain between HDAC inhibitors can alter inhibitory effect on HDAC protein leading to influence gene expression, thereby enhancing high-salinity stress tolerance in different extent.